Family supports and maternal factors of complementary feeding self-efficacy for children aged 6-24 months - Alfin Lailatul Fadilah; Lailatul Muniroh; Dominikus Raditya Atmaka (AcTion: Aceh Nutrition Journal, 2023)
Maternal self-efficacy in parenting is often associated with complementary feeding practices. Maternal and external factors influence the level of maternal self-efficacies. This study aimed to measure the relationship between family supports and maternal factors with complementary feeding self-efficacy for children aged 6-24 months. The survey research has a cross-sectional design. The research subjects were 74 mothers who were selected using simple random sampling. Data collection was carried out in the work area of Kalirungkut Public Health Centers for one month. Family support variables, maternal factors, and maternal self-efficacy were collected using a questionnaire, and then the data on each variable was processed by editing data, coding, and tabulating. The data analysis with Chi-square test and logistic regression on 95% CI. The results of this study were that age (p=0,872), parity (p=0,660), knowledge (p=0,252), informational (p=0,135), and instrumental support (p=1,000) were not related to maternal self-efficacy. There was a significant relationship between education (p=0,040), emotional (p=0,027), and appraisal support (p=0,020) with maternal self-efficacy. Appraisal support is the dominant factor affecting children's complementary feeding self-efficacy (p<0,05; OR=3,711). The conclusion is that education, emotional support, and appraisal support are significantly related, and appraisal support affects complementary feeding self-efficacy.